Pengaruh Abu Terbang Terhadap Sifat-Sifat Mekanik Beton Alir Ringan Alwa - Surya Sebayang; Ratna Widyawati; Muhammad Habibie B. (Jurnal Teknik Sipil, 2012)
Flowing concrete flow under it own weight and maintain homogeneity while filling and passing around congested reinforcement. Lightweight flowing concrete is used to reduce or eliminate the requirement vibration to reduce construction cost, reducing construction time, and and minimize the dead load of the weight of its own. The purpose of this study is to determine and compare the effect of adding the percentage of fly ash in lightweight flowing concrete mixture of the mechanical properties by analyzing workability, bulk density, compressive strength, modulus of elasticity of concrete and setting time. Mix design using the ACI method combined with the method of Hashimoto. The substitution of fly ash to the concrete are 0%, 3%, 6%, 9%, 12%, and 15% of the cement content. Treatment of samples was done by soaking and aerated for 7 days. Compressive strength testing performed on specimens aged 7 days, 28 days and 56 days. From the test results obtained : (1) Effect of fly ash in fresh concrete was increased the workability of the concrete, (2) Additionn of fly ash was increased the initial and final setting time, (3) by using natural sand materials from Tanjung Bintang produce concrete with a weight (mass) concrete slightly exceeded the limit of weight requirements of lightweight concrete (1850 kg/m3), (4) The optimum strength of fly ash lightweight flowing concrete was 22,98 MPa at 56 days age in 6% percentage of fly ash.